Strategy: get arts 35 artists who broke the rules - Weikop, Christian 1970- (Edinburgh University Press, 2021)
Based on close archival research, Christian Weikop uncovers unknown and exciting narratives, as well as artist networks, concerning this provocative 1970 exhibition, held at ECA. The author has previously considered the British press reception of SGA in an article for Tate Papers, but this Studies in Photography-EUP book publication goes far beyond that article and any other scholarship on the exhibition by taking into account the contributions of all 35 artists based in Düsseldorf, and incorporating testimony of individuals who were involved in this landmark exhibition, or who were later engaged in archive exhibitions or recreation projects. Weikop explores the formation of the exhibition in the context of a late 1960s culture of protests and occupations, and demonstrates that SGA was a pivotal ‘Shock of the New’ moment that would leave its mark on art education.
Keywords: Edinburgh International Festival -- 1970 -- Edinburgh; Geschichte 1970; Kunstausstellung; Künstlerisches Werk; Fotografie; Edinburgh; Edinburgh International Festival / (1970); Photography, Artistic; Art / Exhibitions / Pictorial works; Edinburgh International Festival; Art / Exhibitions; Pictorial works